“Sick with worry...” Stories from the front-line of inequality, 2015 - St Vincent de Paul Society
Contains some sobering stories of poverty and inequality in prosperous Australia, finding overwhelmingly that people do not experience poverty because they choose to but as a result of a range of structural causes which push them to the margins. Executive summary In late 2013, the St Vincent de Paul Society published research outlining some startling statistics about poverty in Australia today. Two Australias: A report on poverty in the land of plenty showed that 13 per cent of the population is living in poverty, 1.5 million people are unemployed or underemployed, the bottom fifth of households receive only 2.5 per cent of wages, and a quarter of us live with a long-term health condition or disability. The report concluded that, under Australia’s prosperous veneer, there is a significant group of people who are struggling just to survive.   Behind the numbers are the faces. Following from that quantitative survey, the St Vincent de Paul Society decided to conduct the present research because we wanted to hear the stories of those doing it toughest. Those for whom every day is a battle. Stories from the other Australia.   We sent out a call to our members and volunteers, and over 70 interviews were conducted around the country. When we read the stories, some key themes emerged. These themes will not be a surprise to anyone who is familiar with disadvantage in Australia today: there is a severe shortage of stable, affordable housing; incomes for many are not sufficient for a decent standard of living, and secure work is very hard to find; and Australians living with disability continue to face severe structural barriers to participation. Cutting across all three areas were several further issues: the stigma faced by those on the edge; the inherent insecurity that life entails for many in the other Australia; and the disproportionate impact of poverty on women.   However, what also shone through our research were three remarkable opportunities for change. First, supportive, rights-based services can and do help many people out of poverty. Secondly, people’s overwhelming love for their children presents a wonderful lens through which to see change happen. And, finally, what almost everyone desires above all else is to be able to participate.   Therefore, while it seems there are structural problems around housing, employment and disability that are systemically excluding people, the research shows that the way forward involves better service provision and harnessing people’s keen desire to contribute